1992
DOI: 10.1111/j.1524-4725.1992.tb03675.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Secondary to Recessive Dystrophic Epidermolysis Bullosa: A Report of 4 Patients with 17 Primary Cutaneous Malignancies

Abstract: Four patients with recessive dystrophic epidermolysis bullosa and 17 invasive primary cutaneous squamous cell carcinomas (SCCs) are presented. All skin cancers arose at the site of scarring due to recessive dystrophic epidermolysis bullosa. Three of 17 (18%) primary cutaneous SCCs recurred locally following initial treatment with either surgical excision or wide surgical excision. Patients with recessive dystrophic epidermolysis bullosa are more likely to develop SCCs of the extremities than nonimmunocompromis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This occurs mainly in dystrophic epidermolysis bullosa patients, not only because of recurrent blistering and erosions, but also because of their poor nutritional status. Newman et al (1992), reported an 18% local recurrence rate even after wide local excision of primary squamous cancer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This occurs mainly in dystrophic epidermolysis bullosa patients, not only because of recurrent blistering and erosions, but also because of their poor nutritional status. Newman et al (1992), reported an 18% local recurrence rate even after wide local excision of primary squamous cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Squamous cancer in epidermolysis bullosa has a predilection for limbs, bony prominences, and sites where blistering and scarring are most pronounced. Patients with recessive dystrophic epidermolysis bullosa are more likely to develop squamous carcinomas of the extremities than non-immunocompromised patients (Newman et al 1992). They are more likely to suffer from invasive and metastatic squamous cancers at a much younger age than nonimmunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that SCCs in RDEB are usually histologically well differentiated, they often have a poor prognosis because of the high frequency of occurrence, rapid invasiveness, and development of distant metastases 3 . They are also often multiple 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…3 They are also often multiple. 4,5 The pathogenesis of developing SCCs in patients with RDEB is not well established. RDEB is caused by mutations in the type VII collagen gene ( COL7A1 ) 6 and, in these patients, it has been demonstrated that the NC1 domain of type VII collagen is associated with a high risk for the development of SCC.…”
Section: Scc Represents a Major Clinical Complication Of Rdeb-hsmentioning
confidence: 99%
“…Carcinogenesis represents a major clinical complication for some epidermolysis bullosa patients. [2][3][4] The cumulative risk of squamous cell carcinoma is 39.6% by the age of 30 in RDEB-HS. 1 Skin cancer primarily affects the extremities; the side of the neck site seen in the present patient is quite unusual.…”
Section: Reportmentioning
confidence: 99%